Isoliquiritigenin Inhibits Atherosclerosis by Blocking TRPC5 Channel Expression - Jie Qi; Jianguo Cui; Baobin Mi; Xiaohong Yan; Wenwen Xu; Hui Ma; Qingtan Zhang; Fang Xu (Cardiovascular Therapeutics)
Isoliquiritigenin (ISL) is a flavonoid isolated mainly from the licorice plant, a traditional Chinese herb. ISL has shown anticancer, anti-inflammatory, antioxidant, and antidiabetic activities. However, the pharmaceutical effects of ISL on atherosclerosis are seldom explored. In this study, we used apolipoprotein E (ApoE) knockout mouse model and angiotensin II- (Ang II-) stimulated vascular smooth muscle cells (VSMCs) to elucidate the pharmacological mechanism of ISL to inhibit atherosclerosis. We found that in ApoE−/− mice ISL could attenuate atherosclerotic lesion, reduce serum lipid levels, and inhibit TRPC5 expression. In vitro, ISL inhibited Ang II-stimulated proliferation of VSMCs and suppressed Ang II-induced TRPC5 and PCNA expressions in a dose-dependent fashion. In conclusion, our findings provide novel insight into the pharmacological effects of ISL on atherosclerosis and suggest that ISL is beneficial for cardiovascular protection.